1997
DOI: 10.1070/qe1997v027n09abeh001053
|View full text |Cite
|
Sign up to set email alerts
|

Beat spectrum of a dye laser generating three nonequidistant modes

Abstract: Few studies using high frequencies have been carried out on the sono-TiO 2 process, and consistent results based on the specific experimental conditions have not been reported thus far. Therefore, in the present work the effects of power density and dose on the kinetic constant of diethyl phthalate at 500 and 35 kHz using TiO 2 have been evaluated. The slopes of kinetic constants depending on the power density regardless of TiO 2 were increased and they were shown to be linear. However, the enhancement percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The multiple-frequency model is presented here to cover both cases, simultaneously. It is demonstrated that the coupling of satellite lines generates a train of short pulses of a duration in the order of picoseconds within experimental results [2,15]. If the number of satellite lines is increased in the frequency domain, then shorter pulses will be created in the time domain by approaching the injection-locking borders [6,16].…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…The multiple-frequency model is presented here to cover both cases, simultaneously. It is demonstrated that the coupling of satellite lines generates a train of short pulses of a duration in the order of picoseconds within experimental results [2,15]. If the number of satellite lines is increased in the frequency domain, then shorter pulses will be created in the time domain by approaching the injection-locking borders [6,16].…”
Section: Introductionmentioning
confidence: 70%
“…The first image satellite line α − is now produced by the FWM process between the strong electric field of the central mode α L0 and the amplified input signal α + proportional to the input signal amplitude β S . The central-mode frequency of the free-running laser ω L0 is to shift by the second-order value ω L correct to β 2 S , so that the central-mode frequency of the laser amplifier ω L is now equal to [10,15]…”
Section: Laser Amplifier Structurementioning
confidence: 99%
See 2 more Smart Citations